2018
DOI: 10.1634/theoncologist.2017-0342
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutational Burden Guides Therapy in a Treatment Refractory POLE-Mutant Uterine Carcinosarcoma

Abstract: Uterine carcinosarcoma is an uncommon and aggressive histologic variant of endometrial carcinoma with a poor prognosis.Inactivating DNA polymerase ɛ () mutations have been associated with high tumor mutational burden (TMB) and response to immune checkpoint inhibition.To the authors' knowledge, this is the first report of response to immune checkpoint inhibitor therapy in a patient with uterine carcinosarcoma.This case further supports expanding genomic profiling to include assessment of tumor mutational burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Genomic analyses have shown that particular mutational signatures can contribute to high TMB independently from MSI status. These include BRCA1/2 (breast cancer genes 1 and 2) and APOBEC deficiency, neoantigen load, ultraviolet rays exposure and mutations affecting TP53 and polymerase e (POLE) (supplementary Figure S2, available at Annals of Oncology online) [7,59,70,[90][91][92][93][94][95].…”
Section: Annals Of Oncologymentioning
confidence: 99%
“…Genomic analyses have shown that particular mutational signatures can contribute to high TMB independently from MSI status. These include BRCA1/2 (breast cancer genes 1 and 2) and APOBEC deficiency, neoantigen load, ultraviolet rays exposure and mutations affecting TP53 and polymerase e (POLE) (supplementary Figure S2, available at Annals of Oncology online) [7,59,70,[90][91][92][93][94][95].…”
Section: Annals Of Oncologymentioning
confidence: 99%
“…34,35 Furthermore, it has also been reported that POLEmutant endometrial and colorectal tumors had a high somatic mutation burden, elevated expression of immune checkpoint genes and increased lymphocytic infiltration, [36][37][38][39][40][41][42][43] and therefore immune checkpoint inhibitors was recommended for treating cancers with POLE-mutations. 41,44 Similar recommendation was also demonstrated in mismatch repair (MMR) deficient cancers regardless of the cancers' tissue of origin. 45 In this phase II clinical trial, clinical benefit was observed in 53% patients, half of whom also carried germline mutations in MMR genes.…”
Section: Discussionmentioning
confidence: 59%
“…Our finding is consistent with recent findings that POLE mutations can contribute to susceptibility to a broad cancer spectrum including OC . Furthermore, it has also been reported that POLE ‐mutant endometrial and colorectal tumors had a high somatic mutation burden, elevated expression of immune checkpoint genes and increased lymphocytic infiltration, and therefore immune checkpoint inhibitors was recommended for treating cancers with POLE ‐mutations . Similar recommendation was also demonstrated in mismatch repair (MMR) deficient cancers regardless of the cancers’ tissue of origin .…”
Section: Discussionmentioning
confidence: 75%
“…This point may suggest the beneficial effect of PD-L1 blockade in cases with UCS. Recently the first case was reported as anti PDL-1 (pembrolizumab) response in DNA polymerase epsilon (POLE)mutant UCS [27]. Due to the atypical pathogenesis and poor prognosis despite conventional adjuvant chemotherapies, it is imperative to try to better understand the molecular pathogenesis of UCS and to find targeted therapies.…”
Section: Discussionmentioning
confidence: 99%